Commemorating insulin's centennial: engineering insulin pharmacology towards physiology. (August 2021) - Kurtzhals, Peter; Nishimura, Erica; Haahr, Hanne; Høeg-Jensen, Thomas; Johansson, Eva; Madsen, Peter; Sturis, Jeppe; Kjeldsen, Thomas
Abstract : The life-saving discovery of insulin in Toronto in 1921 is one of the most impactful achievements in medical history, at the time being hailed as a miracle treatment for diabetes. The insulin molecule itself, however, is poorly amenable as a pharmacological intervention, and the formidable challenge of optimizing insulin therapy has been ongoing for a century. We review early academic insights into insulin structure and its relation to self-association and receptor binding, as well as recombinant biotechnology, which have all been seminal for drug design. Recent developments have focused on combining genetic and chemical engineering with pharmaceutical optimization to generate ultra-rapid and ultra-long-acting, tissue-selective, or orally delivered insulin analogs. We further discuss these developments and propose that future scientific efforts in molecular engineering include realizing the dream of glucose-responsive insulin delivery. Highlights: Pharmacokinetically tailored insulin has been rationally designed by molecular structural engineering and/or pharmaceutical formulation to improve glucose control and convenience for people with diabetes. Novel mechanisms for protracted insulin action based on reduced plasma clearance hold promise to enable once-weekly subcutaneous and once-daily oral basal insulin delivery. Hepato-preferential insulin analogs can be designed by tailoring molecular size and receptor affinity to provide more physiological insulin replacement. Successful oral insulin delivery has been achieved in early clinical trials but is still hampered by low bioavailability. Clinical trials have been initiated with glucose-sensitive analogs chemically engineered to switch between active and inactive conformations or to undergo glucose-dependent clearance, thus giving hope that a 'smart insulin' is within reach.